Samaritans, Biblical Studies, and Ancient Judaism Recent Trends - Chalmers, Matthew (2021)
In this article, I survey recent trends in Samaritan studies, with a particular focus on biblical studies and the interactions of Samaritan Israelites with other religious traditions. While remaining entrenched in discussion of the origins of Samaritans, scholars have firmly embraced the idea of processual Samaritan identity, emerging over time and in a non-genealogical sense alongside and interwoven with Judean/Jewish self-definition. Extensive work clusters, in particular, at three nodes: the study of Hebrew-language scriptures, archaeological excavations, and the remodelling of identity-production in a constructivist form. I also sketch out the directions in which the field is moving, with growing and productive emphasis on Aramaic, Arabic, and late antiquity. Finally, I identify some of the quirks of Samaritan studies as it might be encountered, in particular a continued effort to salvage Samaritans for biblical studies, somewhat intermittent interdisciplinarity, and practices of engagement with Samaritan Israelites themselves.
Keywords: Samaritans; Qumran; Late Antiquity; Israelites; Identity; Ethnicity; Dead Sea Scrolls; Constructivism; Biblical Studies; Archaeology; Aramaic; Arabic